Alcohol-Based Hand Sanitizers: Does Gelling Agent Really Matter? - Ivana d’Angelo; Romina Provenzano; Ettore Florio; Chiara Pagliuca; Giuseppe Mantova; Elena Scaglione; Mariateresa Vitiello; Roberta Colicchio; Paola Salvatore; Francesca Ungaro; Fabiana Quaglia; Agnese Miro (Gels, 2022)
Hand hygiene, social distancing, and face covering are considered the first protection against Coronavirus spreading. The high demand during the COVID-19 emergency has driven a frenetic production and marketing of hand sanitizer gels. Nevertheless, the effect of the gelling agent and its amount on the effectiveness of alcohol-based hand sanitizers (ABHSs) needs to be clarified. We presented a systematic study on the effect of the characteristics and concentration of the most employed excipients on the properties and antimicrobial activity of ABHSs. Three different gelling agents, carbopol, hydroxypropylmethylcellulose (HPMC), and hydroxyethylcellulose (HEC), at four different concentrations were used to prepare ABHSs. Viscosity, spreadability, delivery from commercial dispensers, evaporation rate, rubbing time, and hand distribution of the ABHSs were then explored. Biocidal activity of selected ABHSs was evaluated in vitro on ATCC and clinical strains. The studied ABHS can be considered bioactive and comfortable. Nevertheless, the cellulose polymers and ethanol interactions led to a slight but significant reduction in the biocidal activity compared with carbopol-based formulations. Our results underline the importance of the gelling agent properties and support the choice of carbopol as one of the best thickener agents in ABHS formulations.